Charakter prawny polecenia doprowadzenia skazanego w celu odbycia kary - Gmaj, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article presents the author’s views on the legal nature of the institution of bringing a convict to serve his sentence in connection with the amendment to the Executive Penal Code, which came into force on January 1, 2023. The amendment introduced regulated differently the activities of bringing a convict to serve his sentence. Previous regulations in this regard did not raise major doubts, and the mere order to bring a convict to the Detention Center did not have the character of procedural decisions. These were technical-administrative actions carried out by the President of the Court (the Chairman of the Department, an authorized Judge, and in many Courts by the Head of the Executive Section or the Judgment Execution Section). The amendment to the legislation may lead to discrepancies in the assessment of the legal nature of this institution, the assessment of which after the amendment is not clear and requires a new interpretation. In the author’s opinion, the order to bring a convict to serve a prison sentence is also substantive and procedural, and not just administrative. Such a concept is supported by the fact that this order involves the actual detention and incarceration of the convict in a Detention Center or prison, which is related to the actual deprivation of liberty. Thus, there are elements of a procedural action here that go far beyond the administrative-technical sphere. Since there is an actual detention and incarceration of the convict, the convict should be allowed to challenge such a decision, and therefore this will be another procedural guarantee in the executive proceedings, as well as an action that realizes the constitutional rights of the individual, including the convict. These new views on the legal nature of the institution of an order to bring a convict to serve a prison sentence, in connection with the changes made in this regard, would lead to the evolution of executive criminal law and its modernization, but not necessarily to the rationality of its application
Keywords: enforcement procedure; imprisonment; the first instance court; judical decision; bringing the convicted person to serve the sentence